ChemInform Abstract: Scandium‐Substituted Na3Zr2(SiO4)2(PO4) Prepared by a Solution‐Assisted Solid‐State Reaction Method as Sodium‐Ion Conductors. Issue 39 (September 2016) - Ma, Qianli; Guin, Marie; Naqash, Sahir; Tsai, Chih‐Long; Tietz, Frank; Guillon, Olivier
Abstract: Polycrystalline Na3+x Scx Zr2‐x (SiO4 )2 (PO4 ) (NSZSPx, x = 0—0.6) are fabricated on a laboratory scale (10 g—1 kg) by precipitation from stoichiometric aqueous solutions of NaNO3, Sc2 O3, ZrO(NO3 )2, Si(O‐Ac)4, and NH4 H2 PO4 followed by calcination (800 °C, 3 h), ball milling (2 d), and final sintering (1250—1300 °C, 5 h).